Knowledge and attitutde of Universiti Malaysia Sabah (UMS) Muslim students on their practices of choosing halal food products and premises - Abdul Latif, Mariam; Harris, Hazriani; Ab Rahman, Suhaimi (Research Novelty Publisher, 2019)
The objective of this study was to examine the knowledge and attitudes of Muslim students on their practices of choosing halal food. It was conducted on 367 Muslim students who are currently pursuing undergraduate studies in Universiti Malaysia Sabah (UMS). Random sampling method was used to recruit the respondents. The questionnaire used was a closed-ended and divided into four parts: A) The Practices of Choosing Halal Food, B) The Knowledge on Concept of Halal Food, C) The Attitudes on Choosing Halal Food, and D) Respondent’s Demographic. All data were analysed using Statistical Package for Social Science (SPSS) Version 16.0. This study showed the practices of choosing halal food among the respondents were satisfactory. The respondents’ knowledge on halal food concept was good. The respondents’ attitudes on choosing halal food were positive. The relationship between knowledge and practices of the respondents were not significant (r=0.04, p>0.05). However, the relationship between their attitudes and practices were found to be significant (r=0.73, p<0.05).